Modified parametric estimation for non-participant of sample selection model - Umi Mahmudah (Terengganu: Universiti Malaysia Terengganu, 2013)
Sample selection model which is introduced in 1979 widely used in economic, social science and decision science fields. However, this model has a disadvantage where only observed participation that was positive (latent variables) which means that bias is occurred in the model. While latent variable that less than or equal to zero(non-participant) unconsidered in studies.